Project management resources and outcomes: a confirmatory factor analysis. Issue 3 (9th January 2020) - Perkins, David; Mathur, Gita; Jugdev, Kam
Abstract : Purpose: The purpose of this paper is to draw on the resource-based view of the firm from strategic management and apply it to a study of competitive advantage in the project management context. Confirmatory factor analysis (CFA) is used to examine the factors that constitute strategic characteristics of project management resources and outcomes of the project management process. Design/methodology/approach: This study gathered data from 437 North American project management professionals using an existing survey tool from prior research involving a smaller sample. Findings: The final model derived from CFA demonstrated construct validity, meaning acceptable convergent and discriminant validity. It showed only minor differences from a prior exploratory factor analysis (EFA). The final model consisted of two factors representing valuable project management characteristics, one factor representing rare project management characteristics, one factor representing inimitable project management characteristics, three factors representing organizational support for project management assets, one factor representing project-level performance and one factor representing firm-level performance. Research limitations/implications: Limitations of the study include self-report bias and the use of a panel for data collection. Practical implications: This study draws managerial attention to project management characteristics that constitute a source of competitive advantage. Originality/value: The study validates a survey tool from previous research, reflects few deviations from factor structure of the prior EFA, and sets the stage for future research to elaborate on the conceptual model. It extends understanding of the characteristics of project management assets that lead to a firm's competitive advantage.